Travel far, pay no fare - Lindbergh, Anne.; Lindbergh, Anne. (New York, NY : HarperCollins Publishers, 1992)
When twelve-year-old Owen finds that his nine-year-old cousin has a magic bookmark, he joins her when she enters different stories in hopes of finding a way to prevent their parents' upcoming marriage.
Keywords: Magic -- Fiction; Remarriage -- Fiction; Cousins -- Fiction; Books and reading -- Fiction